2015
DOI: 10.1002/piq.21185
|View full text |Cite
|
Sign up to set email alerts
|

What Makes an Organization a Great Place to Work in South Korea?

Abstract: The purpose of this study is to identify diverse factors that positively and negatively affect a workplace and to suggest a model for great places to work in South Korean organizational contexts. The research questions guiding the study are (a) What are the most desirable characteristics of a great place to work? and (b) What are the most undesirable characteristics of a bad place to work? An online survey and mobile application with two questions asking about the components of the most desirable and undesirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Nevertheless, 41.3% of Korean workers employed in small-tomedium-size enterprises (SMEs) are seeking opportunities to change and develop their careers in larger organizations (OECD 2017). Although Korean employees prefer to work in larger companies, most Korean career changers, including job-seekers and employees, highly value a strong organizational culture, vision of leaders for people, and talent development when they are choosing between seeking a new job and remaining in their current organization (Park et al 2015). Korean society has been deeply influenced by the country's Confucian cultural tradition, so work practices and networking remain largely male-dominated in Korean organizations (Cooke 2010;Rowley, Kang and Lim 2016).…”
Section: Korean Contextsmentioning
confidence: 99%
“…Nevertheless, 41.3% of Korean workers employed in small-tomedium-size enterprises (SMEs) are seeking opportunities to change and develop their careers in larger organizations (OECD 2017). Although Korean employees prefer to work in larger companies, most Korean career changers, including job-seekers and employees, highly value a strong organizational culture, vision of leaders for people, and talent development when they are choosing between seeking a new job and remaining in their current organization (Park et al 2015). Korean society has been deeply influenced by the country's Confucian cultural tradition, so work practices and networking remain largely male-dominated in Korean organizations (Cooke 2010;Rowley, Kang and Lim 2016).…”
Section: Korean Contextsmentioning
confidence: 99%
“…However, these characterizations of great places to work are confounded by a myriad other somewhat idiosyncratic suggestions at the individual, leadership, work group, and organizational levels. At the individual level, factors such as good physical workspace and compensation, recognition, caring human resource, learning and career development opportunities, flexibility, job satisfaction, challenging work, etc., have been suggested to characterize great places to work (Park et al, 2015;Mencl & Lester, 2014;Butler, 2014).…”
Section: Great Places To Work: An Overviewmentioning
confidence: 99%
“…At the leadership level, it is suggested that great places to work have inspiring, authentic, and servant leadership (Henderson, 2011;Love & Singh, 2011;McGee-Cooper & Trammell, 2010). At the group level, factors such as team spirit, mutuality, cohesiveness, group focused processes, quality relationship, authentic behavior, collaboration, diversity are stated to signal great places to work (Park et al, 2015;Mencl & Lester, 2014;Crainer, 2014;Taskinen, 2011). Finally, at the organizational level, studies suggest that factors such as low levels of hierarchy, consistent assessment practices, autonomy, focus on employee wellness and engagement, worklife balance, safety orientation, fun work environment, transparency, accountability, civility and networking opportunities, focus on all stakeholders, corporate citizenship behavior, community oriented policies, social goals, and well laid out and easily accessible ethics statement are indicative of great places to work (Hoover & Pepper, 2014;Philipsen, 2014;Hinkin & Tracey, 2010;Bakker, 2010;Bernardi, Bosco & Vassill, 2006;DeCotiis, Sullivan, Hyatt, & Avery, 2004;van Marrewijk, 2004;Joyce, 2003).…”
Section: Great Places To Work: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations